2022
DOI: 10.1002/jcla.24534
|View full text |Cite
|
Sign up to set email alerts
|

The utility of SARS‐CoV‐2 nucleocapsid protein in laboratory diagnosis

Abstract: By the end of December 2019, several unknown pneumonia cases who manifested as respiratory syndromes and fever were found in Wuhan, China. 1 Subsequently, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel virus classified as β-coronavirus genus, was identified in bronchoalveolar lavage fluid and other respiratory samples obtained from patients with unknown pneumonia. 2 As of March 31, 2022, about 485 million confirmed cases have been reported worldwide with more than 6.1 million deaths. 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…RAT performance did not significantly change between Omicron sublineages BA.2, BA.5 and XBB.1. This is aligned with current knowledge given that RATs target the nucleocapsid protein [21], while majority of mutations in SARS-CoV-2 variants of concern (VOC) occur in the spike protein [22]. These findings reassure us that the performance of RAT is not affected by the emergence of new variants and sublineages.…”
Section: Discussionsupporting
confidence: 74%
“…RAT performance did not significantly change between Omicron sublineages BA.2, BA.5 and XBB.1. This is aligned with current knowledge given that RATs target the nucleocapsid protein [21], while majority of mutations in SARS-CoV-2 variants of concern (VOC) occur in the spike protein [22]. These findings reassure us that the performance of RAT is not affected by the emergence of new variants and sublineages.…”
Section: Discussionsupporting
confidence: 74%
“…Despite the slow evolutionary changes that may affect the antigenic properties of the N protein, the majority of studies on the development of N-targeting diagnostics suggest that serum or plasma N levels may be used to detect SARS-CoV-2 and predict the COVID-19 outcome, and the specificity of such antigenic tests may reach 100% [ 91 ]. Thus, the ACTIV-3/TICO Group study revealed a strong positive correlation of pulmonary disease severity or exacerbation risks with plasma N levels, as well as an association of this indicator with the lack of anti-S antibodies, male sex and renal failure [ 92 ].…”
Section: Mutability Of N Sequences and Its Implication For The Perfor...mentioning
confidence: 99%
“…4 The nucleocapsid protein (N protein) is the most abundant protein antigen in SARS-CoV-2 and shows lower mutation rates among different variants compared to the spike protein. 5 As these features enable more sensitive measurements and a more reliable detection of different virus variants by the same antibodies, the N protein is commonly used as a target antigen in microtiter-plate enzyme-linked immunoassays (ELISA) and lateral flow immunoassays (LFA) intended for point-of-care testing. 6 Various other assay formats and detection schemes for the diagnosis of SARS-CoV-2 have been reviewed recently.…”
Section: Introductionmentioning
confidence: 99%